2018
DOI: 10.1097/iae.0000000000002198
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Choriocapillaris Flow in Eyes With Type 3 Neovascularization and Age-Related Macular Degeneration

Abstract: Eyes with unilateral Type 3 NV illustrated increased CC nonperfusion versus fellow nonneovascular eyes. These results suggest that choroidal ischemia may play an important role in the development of Type 3 NV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
75
2
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 114 publications
(83 citation statements)
references
References 47 publications
5
75
2
1
Order By: Relevance
“…Borrelli et al report in a retrospective analysis that a significantly greater percentage of non-perfused areas in the choriocapillaris can be measured by OCT-A in eyes with type 3 neovascularisation compared with their healthy partner eyes. These healthy partner eyes also show more non-perfused areas in the choriocapillaris than the healthy partner eyes of patients with type 1 or 2 neovascularisation [21]. These results are consistent with previous studies in which significantly thinner subfoveal choroid was found by OCT (enhanced depth imaging) in eyes with type 3 neovascularisation compared with eyes with typical exudative AMD [22] and healthy eyes [23].…”
Section: Discussionsupporting
confidence: 91%
“…Borrelli et al report in a retrospective analysis that a significantly greater percentage of non-perfused areas in the choriocapillaris can be measured by OCT-A in eyes with type 3 neovascularisation compared with their healthy partner eyes. These healthy partner eyes also show more non-perfused areas in the choriocapillaris than the healthy partner eyes of patients with type 1 or 2 neovascularisation [21]. These results are consistent with previous studies in which significantly thinner subfoveal choroid was found by OCT (enhanced depth imaging) in eyes with type 3 neovascularisation compared with eyes with typical exudative AMD [22] and healthy eyes [23].…”
Section: Discussionsupporting
confidence: 91%
“…() found that nonperfused CC area detected on OCT‐A correlated to decreased visual acuity in a group of eyes with drusen and pseudodrusen; Borrelli et al. () observed a correlation between FVs area and N1 multifocal electroretinogram implicit times in iAMD, thus supporting the hypothesis of an association between CC perfusion and photoreceptor function.…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, a higher average CC signal void size was reported in eyes with early and iAMD and type 3 neovascularization in the fellow eye versus early and iAMD and type 1 or 2 neovascularization in the fellow eye (Borrelli et al. ,b,c). It is clearly established that patients with nAMD in one eye have a higher risk of developing nAMD in the fellow eye, therefore, these data may support the hypothesis that CC impairment could drive the development of neovascular form of AMD.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies assessed the retinal and choroidal vasculature in eyes with iAMD and showed that iAMD eyes are characterized by a reduced SCP and CC perfusion density, especially in the presence of nascent geographic atrophy or neovascularization in the fellow eye. 21,[25][26][27][28] The average signal void size of the CC and PNPCA were recently characterized in eyes with iAMD using spectral domain optical coherence tomography angiography. 21 In the latter study, OCTA data from 42 iAMD eyes (42 patients) and 20 eyes from 20 healthy individuals were retrospectively collected.…”
Section: Discussionmentioning
confidence: 99%